A review of efficacy of platelet-rich plasma in the treatment of intrabony periodontal defects - Hamid Moghaddas; Omid Moghaddas (مجله دانشکده دندانپزشکی اصفهان, 2013)
Introduction: Use of growth factors has been evaluated in regenerative treatments and it has been shown that they are effective in proliferation, chemotaxis, differentiation, and synthesis of extracellular matrix and cells responsible for wound healing, enhancing the repair and regeneration of the periodontium. The aim of this literature review is to evaluate the effects of platelet-rich plasma (PRP) in combination with different graft materials, with and without membranes, in regenerative therapy of intrabony defects.Review of Report: Electronic search was carried out in PUBMED and MEDLINE for randomized clinical trials which have used platelet-rich plasma in the treatment of intrabony defects with a minimum follow-up period of 6 months. Articles were collected until the end of April 2011. Inclusion criteria in the evaluated research studies consisted of defects at least 3 mm in depth and pockets at least 5 mm in depth. Twenty articles were confirmed and evaluated in this review. The parameters evaluated were probing depth changes, defect fill and an increase in clinical attachment level.Conclusion: Within the limitations of studies carried out in this respect it can be concluded that use of PRP has not exert a positive adjunctive effect on improving clinical parameters in regenerative treatments of intrabony defects when used in combination with membranes; however, when it has not been used with a membrane, use of PRP along with bone grafts has led to positive results. Key words: Clinical trial, Periodontal disease, Platelet-rich plasma